The Impact of the Risk Perception of COVID-19 PANDEMIC on College Students’ Occupational Anxiety: The Moderating Effect of Career Adaptability - Ning, Jinhui; Yin, Shi; Tang, Ruonan (International Journal of Statistics in Medical Research, 2024)
In order to understand the changes in college students’ risk perception and occupational emotion under major public health events and to explore the influencing factors of college graduates’ employment guidance, 578 college students were surveyed by questionnaire to explore the impact of the risk perception of COVID-19 pandemic on college students’ occupational anxiety and its internal mechanisms, and to analyze the mediating role of psychological resilience in the impact and the moderating role of career adaptability. The results showed that: (1) there is a significant positive correlation between the risk perception of COVID-19 pandemic and occupational anxiety; there is a significant negative correlation between risk perception and psychological resilience; there is a significant negative correlation between the psychological resilience and occupational anxiety. (2) Psychological resilience plays a mediating role between risk perception and occupational anxiety. (3) Career adaptability plays a negative moderating role between the risk perception of COVID-19 pandemic and occupational anxiety. These results showed that the risk perception of COVID-19 pandemic not only directly aggravates college students’ occupational anxiety, but also indirectly affects occupational anxiety through psychological resilience; Career adaptability significantly alleviats the incremental effect of the risk perception of COVID-19 pandemic on college students’ occupational anxiety. This paper has positive enlightenment on how to improve the employability of college students and alleviate their employment anxiety during major public health events.